2011
DOI: 10.1097/dcr.0b013e31822899a2
|View full text |Cite
|
Sign up to set email alerts
|

Is Colonoscopy Still Mandatory After a CT Diagnosis of Left-Sided Diverticulitis: Can Colorectal Cancer be Confidently Excluded?

Abstract: We recommend routine colonoscopy after an attack of presumed left-sided diverticulitis in patients who have not had recent colonic luminal evaluation. The rate of occult carcinoma is substantial in this patient population, in particular, when abscess, local perforation, and fistula are observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
1
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(95 citation statements)
references
References 17 publications
2
88
1
4
Order By: Relevance
“…However, this advice is based only on expert opinion [11,12]. Recently, results have been published from retrospective studies [13][14][15][16] and one systematic review [17], showing a comparable yield from colonoscopy or other imaging studies after an episode of diverticulitis. In these studies malignant tumours were found in 0-2.8% of patients who underwent colonic imaging [13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…However, this advice is based only on expert opinion [11,12]. Recently, results have been published from retrospective studies [13][14][15][16] and one systematic review [17], showing a comparable yield from colonoscopy or other imaging studies after an episode of diverticulitis. In these studies malignant tumours were found in 0-2.8% of patients who underwent colonic imaging [13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…In Australia [64], a slightly increased colon carcinoma rate (2.1%) was found within 1 year of CT-assisted diagnosis of left-sided diverticulitis. A systematic literature search on the benefit of colonoscopy from the perspective of the detection of colon carcinomas up to 24 weeks after CT diagnosis of diverticulitis identified 10 studies with 771 documented patients [65].…”
Section: History-taking Basic Diagnostic Procedures Differential DImentioning
confidence: 99%
“…The vast majority of the studies draw the conclusion that colonoscopy after radiologically-confirmed uncomplicated diverticulitis is unnecessary to exclude malignancy [55][56][57][58][59][60], while it seems to be necessary after radiologically-confirmed complicated diverticulitis because the risk of malignancy in those patients is higher [61].…”
Section: Colonoscopy Following Acute Diverticulitismentioning
confidence: 99%
“…Granlund et al found an increased risk of colonic neoplasia (especially in the left colon) at 12 months but not in the long-term, recommending colonoscopy after an episode of diverticulitis [60]. Lau et al advised routine colonoscopy after an attack of diverticulitis in patients who have not had recent colonic evaluation, since the rate of colonic carcinoma is increased in those patients, especially in patients complaining for complicated diverticulitis [59]. Choi et al found that the yield of advanced colonic neoplasia was substantially higher in patients with acute diverticulitis than in asymptomatic, average-risk individuals.…”
Section: Colonoscopy Following Acute Diverticulitismentioning
confidence: 99%